FASILITAS DAN AKSES YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMNENTUKAN PEMBELIAN PERUMAHAN GRIYA AGUNG PERMATA BABAT LAMONGAN - Miftahul Huda; Ade Hanno W (LPPM UNISDA, 2020)
Every company in marketing certain products implement a wide variety of marketing strategies. Marketing activities essentially focused on products, pricing, and distribution policy of promotion way.The purpose of this study was to investigate about the product attributes of housing facilities and access to consumer decisions.Allegedly facilities as well as access to housing has a role to consumer decision to purchase products Griya Agung Permata Babat Lamongan.From the research that has been tested with a sample of 100 respondents, showed that the F-test analysis results obtained F count of 17.392 was the value of F table at 2.70 so variable facilities (X1) and access to housing (X2) together have a real impact on consumer decision (Y) is variable T test facility (X1) Calculate the value of 2,868 T> T Table of 1.660, t test access to housing (X2) obtained amounted to 3.561 Calculate T> T Table of 1,660.Dari value of two variables the variable access to housing has a more dominant role than the facility with the highest variable T (3.561> 2.868).Based on the research results for the company should pay more attention factor, especially access to housing facilities as its own appeal for consumer. Keywords: facilities, access to housing and consumer decisions